2022
DOI: 10.1159/000521731
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Macular Hole without Vitreomacular Separation

Abstract: Purpose: To investigate the clinical features and treatment outcomes of idiopathic full thickness macular hole (FTMH) without vitreomacular separation (VMS). Methods: Consecutive cases of idiopathic FTMH at one tertiary center from January 2013 to April 2020 was retrospectively recruited. They were separated into two groups according to the findings in optical coherence tomography (OCT): FTMH with VMS and FTMH without VMS. Ophthalmic examinations and OCT were performed pre and postoperatively. The clinical fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Therefore, the cases reported by Takahashi et al 11 may not be the same as those shown here. In a recent study by Ang et al, 10 15 of 124 FTMH eyes (12.1%) operated on over 8 years had broad adhesions to the macula, which seems much higher than the frequency in our report. They speculate that the reason for the high frequency is that a large number of atypical cases are referred to them as regional referral centers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the cases reported by Takahashi et al 11 may not be the same as those shown here. In a recent study by Ang et al, 10 15 of 124 FTMH eyes (12.1%) operated on over 8 years had broad adhesions to the macula, which seems much higher than the frequency in our report. They speculate that the reason for the high frequency is that a large number of atypical cases are referred to them as regional referral centers.…”
Section: Discussionmentioning
confidence: 90%
“…In a report of 26 FTMH eyes with EP, Bae et al 9 found that a significant proportion of MHs with EP manifested relatively broad adhesion of the vitreous to the circumference of the perifoveal area and shallow vitreous detachment outside of it. Recently, Ang et al 10 described 15 FTMH eyes without vitreomacular separation and reported that these patients tended to be younger and had better preoperative visual acuity than patients with classical MH with vitreomacular separation.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were: (1) equivalent spherical diopter < -1.0D and OCT showing a full-thickness retinal break in the macular zone; (2) vitrectomy combined with intraocular gas lling performed in our hospital. Exclusion criteria were: (1) macular holes in both eyes; (2) high myopia macular holes; (3) traumatic macular holes; (4) macular rhegmatogenous retinal detachment; (5) recurrent macular holes or unclosed holes after operation; (6) patients with macular membrane; (7) lamellar macular holes; (8) previous history of other fundus diseases; (9) a history of glaucoma; (10) OCTA image quality value Q < 5. This study was approved by the ethics committee of our hospital.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Idiopathic macular hole (IMH) causes vision degradation, central scotoma, and metamorphopsia due to a full-thickness defect of the neuroretina in the macular foveal area [5]. IMH can be treated by vitrectomy surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation